2013
DOI: 10.1097/hjh.0b013e328363572f
|View full text |Cite
|
Sign up to set email alerts
|

Salt intake in children 10–12 years old and its modification by active working practices in a school garden

Abstract: Our data indicates that children 10-12 years old have a high salt intake that is well above the proposed recommendations and that a strategy based on theoretical and practical education may achieve in some children an important reduction in daily salt intake which, if maintained over time, may assume important public health implications. These results suggest that in those children a more complete theoretical and practical intervention is more productive and efficient towards reduction of salt intake than sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 32 publications
1
42
1
8
Order By: Relevance
“…Three school-based interventions (one of good quality;[40] one of fair quality;[57] one of poor quality [58]) and three worksite-based studies (all of fair quality) were included. [5961] No modelling studies were identified for this section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three school-based interventions (one of good quality;[40] one of fair quality;[57] one of poor quality [58]) and three worksite-based studies (all of fair quality) were included. [5961] No modelling studies were identified for this section.…”
Section: Resultsmentioning
confidence: 99%
“…[58] In the second school based RCT, the practical intervention group achieved a significant net reduction of 0.7g/day compared with the control group. [57] In a cluster RCT in China, education and training significantly reduced salt intake by a mean of −1.9 g/day in 279 school children (and −2.9 g/day in adult family members). [40]…”
Section: Resultsmentioning
confidence: 99%
“…At this point, we cannot offer an explanation for the influence on these results of early-life determinants or other proposed contributors to accelerated vascular aging as (short-term) BP variability [44] or salt consumption (recent studies in Portugal have reported the average individual salt consumption as reaching 10.7 g/day in adults, and 7.8 g/day in 10-12-year-old children [45,46]). …”
Section: Early Vascular Agingmentioning
confidence: 94%
“…19 In 10-to 12-year-old Portuguese children, 24-hour urinary sodium excretion showed an average salt intake of 7.8 g/d. 20 Similarly, a study in Australian private school children aged 5 to 13 years, which also collected 24-hour urine samples, showed an average salt intake of 6.0 g/d. 21 A review by Brown et al 22 of 41 reports from 20 countries that had included salt intake as an outcome measure showed that in all age groups, in both sexes, in different countries throughout the world salt intake in children is high.…”
Section: Discussion Dietary Salt Intakementioning
confidence: 99%